2019
DOI: 10.1111/1753-0407.13000
|View full text |Cite
|
Sign up to set email alerts
|

Assessing different anthropometric indices and their optimal cutoffs for prediction of type 2 diabetes and impaired fasting glucose in Asians: The Jinchang Cohort Study

Abstract: Background: To study the association between anthropometric measurements and the risk of diabetes and impaired fasting glucose (IFG) and compare body mass index (BMI), waist circumference (WC), and waist-to-height ratio (WHtR) to determine the best indicator and its optimal cutoffs for predicting type 2 diabetes and IFG.Methods: A Chinese prospective (2011-2019) cohort named the Jingchang cohort that included 48 001 participants was studied. Using Cox proportional hazard models, hazard ratios (HRs) for inciden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 36 publications
3
17
0
Order By: Relevance
“…In our study, the diagnostic values of WHpR and WHtR in identifying high risk people for DM were relatively similar. The diagnostic value of WHtR in Chinese cohort study was reported 0.679 that was in parallel with our nding(AUC: 0.666) [36].A recent study in middle east region showed WHtR can better predict the risk of DM and also HTN [37]. Finding from a population based study of 1852 Iranian males aged ≥ 20 years showed WHtR was a strong predictor for developing type 2 diabetes in the future [29].…”
Section: Roc Curve Analysissupporting
confidence: 84%
“…In our study, the diagnostic values of WHpR and WHtR in identifying high risk people for DM were relatively similar. The diagnostic value of WHtR in Chinese cohort study was reported 0.679 that was in parallel with our nding(AUC: 0.666) [36].A recent study in middle east region showed WHtR can better predict the risk of DM and also HTN [37]. Finding from a population based study of 1852 Iranian males aged ≥ 20 years showed WHtR was a strong predictor for developing type 2 diabetes in the future [29].…”
Section: Roc Curve Analysissupporting
confidence: 84%
“…Their findings further suggest that IR is closely related to pre-diabetes. BMI is the simplest anthropometric indicator, and it is often used to assess obesity and the risk of metabolic diseases [ 31 ]. TyG-BMI is a newly developed obesity-related parameter in recent years.…”
Section: Discussionmentioning
confidence: 99%
“…This may be partly attributed to the fact that only studies published in English were included. The risk of obesity associated disease is increased in Asian populations at a lower BMI compared to other ethnic groups, 114,115 with lower BMI cutoffs for overweight and obesity across Asian‐Pacific countries 116–118 . The inclusion criterion for this review rendered several studies targeted at addressing overweight and obesity in men from Asian countries ineligible due to having a lower BMI criterion 119–126 …”
Section: Discussionmentioning
confidence: 99%